Meningkatkan Kemandirian Belajar Melalui Metode PBL Materi Mengembangkan Budaya Kasih Fase F Kelas XI SMA Negeri 2 Sekayam - Paulina Titin (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Children's education is first of all the responsibility of parents, but schools and the Church are also involved in it. The role of parents, the role of society, the role of the Church, and the role of schools are the pillars of education. From the existing problems in PAK learning in class XI IPS 1 SMA Negeri 2 Sekayam to increase learning independence and good learning outcomes, this study aims to improve and improve the quality of learning in class XI IPS 1 SMA Negeri 2 Sekayam and help empower educators in solving learning problems in the form of innovative learning strategies that can be utilized by other educators who have similar problems. The method the author uses Problem-based learning (PBL) is a learning model in which students are faced with real problems and directed to solve them through investigation and problem solving. The goal is to develop higher-order thinking skills, inquiry, and learner confidence. In this classroom action research, researchers emphasize the dimension of independence based on the importance of character building and strong mental attitudes in the younger generation, especially in facing complex global challenges. This type of research is Classroom Action Research (PTK) which is carried out in collaboration between Catholic religious education teachers and researchers, the data is presented in quantitative descriptive. Data analysis techniques used Observation is a method or way to analyze and make systematic records of behavior to see or observe individuals or groups directly and draw conclusions by making conclusions from the results of research that refers to the formulation of the problem. The use of the Problem Based Learning model according to the syntax which includes orienting students to the problem, organizing students to learn, guiding individual and group investigations, developing and presenting results, analyzing and evaluating the problem solving process, is effective in helping to increase learning motivation and independence of students on the material of developing a culture of love in class XI IPS 1 SMA Negeri 2 Sekayam.